Evidence for actin filament-microtubule interaction mediated by microtubule-associated proteins (The Rockefeller University Press, 1978)
We have used low shear viscometry and electron microscopy to study the interaction between pure actin filaments and microtubules. Mixtures of microtubules having microtubule-associated proteins (MAPs) with actin filament have very high viscosities compared with the viscosities of the separate components. MAPs themselves also cause a large increase in the viscosity of actin filaments. In contrast, mixtures of actin filaments with tubulin polymers lacking MAPs have low viscosities, close to the sum of the viscosities of the separate components. Our interpretation of these observations is that there is an interaction between actin filaments and microtubules which requires MAPs. This interaction is inhibited by ATP and some related compounds. Electron micrographs of thin sections through mixtures of actin and microtubules show numerous close associations between the two polymers which may be responsible for their high viscosity.